Introduction: Special Issue of FORUM on Identity - Denise deCaires Narain (Forum, 2010)
'Identity' is a word that we have learned - with good reason - to be wary of. Its suggestion of solidity and fixity makes it a dangerous and divisive concept that elides the flux and instability that characterizes selfhood. In academic discourses, identity has been theorized exhaustively and the idea of the subject as de-centred and constantly shifting is taken-for-granted. But still 'identity' won't go away. Indeed, in some arenas of public culture, 'identity' remains a necessary concept around which to consolidate ideas of selfhood that may not be so readily accommodated in prevailing definitions of the self.